Tidal changes in estuarine systems induced by local geomorphologic modifications - Picado, A. (2010)
Although rising global sea levels will affect the estuarine flooded areas over the coming decades, the local and regional-scale processes will also induce important changes in these coastal systems. The main aim of this work is to investigate possible tidal changes in estuarine systems induced by local geomorphologic modifications, analyzing the particular case of Ria de Aveiro which is in risk of inundation. Located in the Portuguese west coast, this tidally driven lagoon has a large area of mostly abandoned salt pans, which are in progressive degradation caused by the lack of maintenance and by the strong currents which erode their protective walls. To explore possible tidal changes the hydrodynamic model ELCIRC was applied to Ria de Aveiro to simulate and analyse the impact in the lagoon hydrodynamics of this degradation which results in the enlargement of the lagoon flooded area. A high-resolution grid (grid spacing of the order of 1 m) was developed in order to represent the narrow channels adjacent to the salt pans. The hydrodynamic model was then successfully calibrated and assessed for skill for the Aveiro lagoon through comparison between measurements and model results and quantification of the numerical accuracy. The model was subsequently used to investigate the effect of the flooded lagoon area enlargement on tidal propagation in Ria de Aveiro. Simulations were performed for three geomorphologic configurations, representing the reference or present situation and two flooded scenarios. Results were compared through the analysis of tidal currents, tidal asymmetry and tidal prism. The increase of the lagoon flooded area results in an intensification of the tidal currents, tidal prism and tidal asymmetry. Results also indicate that the tidal prism further increases when the flooding depth increases. Otherwise, changes in tidal currents and in tidal asymmetry pattern are negligible with the increase of the flooded area depth. These results indicate that modifications of the flooded area of estuarine systems will result in tidal changes, with an intensification of the actual tidal patterns induced by the enlargement of inundation areas.